2022
DOI: 10.1037/cap0000287
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing multicultural and social justice competencies in Canadian counselling psychology training.

Abstract: Multicultural (MC) and social justice (SJ) training have been areas of exploration within the field of counseling psychology and have gained continual traction within the supporting Canadian literature. This article provides a critique of the current ways in which MC and SJ training are understood within the field of counseling psychology, how they are taught, and how this training is taken up and perceived by graduate students. We discuss the importance of counseling psychology continuing to move beyond dicho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 89 publications
1
15
0
Order By: Relevance
“…Perhaps underpinning such concerns, the participants found that there was a limited focus on MCSJ topics across their graduate training. This finding echoes previous research, as graduate psychology students at both master's and PhD levels have been found to want more focus placed on empowerment, social change, multicultural identities and culturally sensitive models in their supervision course (Jang et al, 2014;Kassan et al, 2015) and general graduate course work (Cohen et al, 2022;Collins et al, 2013;Wada et al, 2020). Despite calls to further increase the focus on diversity and social justice in clinical supervision training and education (R. K. Goodyear et al, 2016;Lund et al, 2020;Peters et al, 2022), the doctoral student SITs' experiences exemplify that there is still much to do in this area.…”
Section: Culturally Responsive and Socially Just Supervisorsupporting
confidence: 78%
See 1 more Smart Citation
“…Perhaps underpinning such concerns, the participants found that there was a limited focus on MCSJ topics across their graduate training. This finding echoes previous research, as graduate psychology students at both master's and PhD levels have been found to want more focus placed on empowerment, social change, multicultural identities and culturally sensitive models in their supervision course (Jang et al, 2014;Kassan et al, 2015) and general graduate course work (Cohen et al, 2022;Collins et al, 2013;Wada et al, 2020). Despite calls to further increase the focus on diversity and social justice in clinical supervision training and education (R. K. Goodyear et al, 2016;Lund et al, 2020;Peters et al, 2022), the doctoral student SITs' experiences exemplify that there is still much to do in this area.…”
Section: Culturally Responsive and Socially Just Supervisorsupporting
confidence: 78%
“…Within a Canadian context, counselling psychologists have long been interested in and committed to addressing diversity and social justice issues in all areas of clinical practice (Cohen et al, 2022; Ginsberg & Sinacore, 2015). While the importance and benefit of attending to and addressing MCSJ issues and factors in supervision have been detailed (e.g., Falender & Shafranske, 2014; Phillips et al, 2017; Wilcox et al, 2022), little is known about how doctoral student SITs develop these same abilities.…”
mentioning
confidence: 99%
“…Namely, interest in internationalization in Western regions may translate into a greater acceptance of alternative and indigenous theories and a move away from Western assumptions about human functioning. This interest has translated into additional courses and a greater focus on multicultural training or indigenous theories in North American training programs (American Psychological Association, 2017a , b ; Canadian Psychological Association, 2017a , b ; Cohen et al, 2021 ; Gregus et al, 2020 ).…”
Section: Students’ Traditional Involvement In International Psychologymentioning
confidence: 99%
“…This can include behaviors like responding faster and more often to clients from an outgroup, but with an unconscious intention to minimize contact or end it as soon as possible without obviously looking discriminatory (completely avoiding contact could be seen as inconsistent with being an egalitarian practitioner). While there has been a considerable push toward increasing cultural competence and awareness of implicit prejudices in counseling psychologists to help combat practitioner discrimination (Cohen et al, 2022), it is important to recognize that, despite being highly touted, such training has usually been found to be ineffective or minimally effective with real-world outcomes (Paluck et al, 2021; also see Duguid & Thomas-Hunt, 2015; Legault et al, 2011). Therefore, until more effective antibias training is developed, the onus is on practitioners to ensure that they learn how to treat clients without aversive bias.…”
Section: Discussionmentioning
confidence: 99%